Pengaruh Penjualan, Total Utang, dan Biaya Produksi terhadap Laba Bersih pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di BEI - Prandika, Harisma Triana; Yulia, Iis Anisa; Rumna, Rumna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to determine the effect of Sales, Total Debt, and Production Costs on Net Income (Case Study on Primary Consumer Goods Sector listed on the IDX in 2024). The sample used in this study were primary consumer goods sector companies that met the research criteria and obtained 27 companies. Data was collected using purposive sampling method which is included in Non-Probability Sampling and hypothesis testing using multiple linear regression method. The results of this study indicate that Sales, Total Debt, and Production Costs partially have a significant effect on Net Income. The F test results show that simultaneously Sales, Total Debt, and Production Costs have a significant effect on Net Income.